Use of Different Kinds of Solutes Alternative to Sucrose in Osmotic Dehydration of Yacon - Brochier, Bethania (2015)
The present work aimed to evaluate glycerol, maltodextrin, polydextrose and sorbitol for the osmotic dehydration of yacon for diabetics, keeping its properties as prebiotic. Osmotic dehydration was carried out using a yacon to 33% concentrated syrup weight ratio of 1:12, with magnetic stirring at 23°C and atmospheric pressure. The best results were achieved for glycerol and sorbitol with 80 ± 4% and 81± 1% of water removal and increase of 3.73 ± 0.11 and 4.30 ± 0.16 times in total soluble solids respectively. Maltodextrin did not promote dehydration.